(untitled) - Feder, Harold A. (New York, 1990)
Succeeding as ann expert witness contains all the information you need to get started, or to enhance your existing skills as an expert. Learn more about what to do, how to prepare, and what to expect. The author is a noted trial lawyer who has achieved favorable results by retaining expert witnesses throughout his trial career
Keywords: Evidence, Expert,Chứng cứ, chuyên gia,Witnesses,Nhân chứng; United States,Hoa Kỳ,United States,Hoa Kỳ